Persepsi Petani Terhadap Peranan Kelompok Tani sebagai Tempat Belajar, Unit Produksi, dan Wadah Kerjasama (Studi Kasus : Dusun Tambua Desa Bonto Marannu Kecamatan Lau Kabupaten Maros) - Minarni Minarni; Mohammad Anwar Sadat; Andi Nur Imran (Jurnal Agribis, 2021)
This study aims to determine farmers’ percesptions of the role of farmer groups as a place of learning, production units, and a forum for collaboration case studies: Tambua Hamlet, Bonto Marannu Village, Lau District, Maros Regency. The study was conducted in january – marc 2021, using a proportional random sampling technique with a sample of 30 farmers who are members of farmers groups. Data analysis used percentage and interval calculation methods. The results showed: the place of learning is in the category of good perception because farmers feel it is helped in solving the problems faced in their farming and with the existence of a place of learning can increase knowledge and skills in the field of farming. Meanwhile, the production units is in the category of fairly good perceptions, this is due to the uneven distribution of production inputs and agricultural equipment. And for the cooperation forum which is in the good category, in general, farmers show a positive perception of the cooperative unit, this is reinforced by the actions of group members helping each other.